Migrating legacy software to the cloud: approach and verification by means of two medical software use cases. (3rd March 2015) - Maenhaut, Pieter‐Jan; Moens, Hendrik; Ongenae, Veerle; De Turck, Filip
Summary: Cloud computing is a technology that enables elastic, on‐demand resource provisioning, allowing application developers to build highly scalable systems. Multi‐tenancy, the hosting of multiple customers by a single application instance, leads to improved efficiency, improved scalability, and less costs. While these technologies make it possible to create many new applications, legacy applications can also benefit from the added flexibility and cost savings of cloud computing and multi‐tenancy. In this article, we describe the steps required to migrate existing applications to a public cloud environment, and the steps required to add multi‐tenancy to these applications. We present a generic approach and verify this approach by means of two case studies, a commercial medical communications software package mainly used within hospitals for nurse call systems and a schedule planner for managing medical appointments. Both case studies are subject to stringent security and performance constraints, which need to be taken into account during the migration. In our evaluation, we estimate the required investment costs and compare them to the long‐term benefits of the migration. Copyright © 2015 John Wiley & Sons Ltd.